Human leukocyte antigen haplotype phasing by allele‐specific enrichment with peptide nucleic acid probes. Issue 3 (19th January 2014) - Murphy, Nicholas M.; Pouton, Colin W.; Irving, Helen R.
Abstract Targeted capture of large fragments of genomic DNA that enrich for human leukocyte antigen (HLA) system haplotypes has utility in haematopoietic stem cell transplantation. Current methods of HLA matching are based on inference or familial studies of inheritance; and each approach has its own inherent limitations. We have designed and tested a probe–target‐extraction method for capturing specific HLA haplotypes by hybridization of peptide nucleic acid (PNA) probes to alleles of the HLA‐DRB1 gene. Short target fragments contained in plasmids were initially used to optimize the method followed by testing samples of genomic DNA from human subjects with preselected HLA haplotypes and obtained approximately 10% enrichment for the specific haplotype. When performed with high‐molecular‐weight genomic DNA, 99.0% versus 84.0% alignment match was obtained for the specific haplotype probed. The allele‐specific target enrichment that we obtained can facilitate the elucidation of haplotypes between the 65 kb separating the HLA‐DRB1 and the HLA‐DQA1 genes, potentially spanning a total distance of at least 130 kb. Allele‐specific target enrichment with PNA probes is a straightforward technique that has the capability to improve the resolution of DNA and whole genome sequencing technologies by allowing haplotyping of enriched DNA and crucially, retaining the DNA methylation profile.